Fertility preservation for male patients with childhood, adolescent, and young adult cancer: recommendations from the PanCareLIFE Consortium and the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 2 (February 2021) - Mulder, Renée L; Font-Gonzalez, Anna; Green, Daniel M; Loeffen, Erik A H; Hudson, Melissa M; Loonen, Jacqueline; Yu, Richard; Ginsberg, Jill P; Mitchell, Rod T; Byrne, Julianne; Skinner, Roderick; Anazodo, Antoinette; et al.
Summary: Male patients with childhood, adolescent, and young adult cancer are at an increased risk for infertility if their treatment adversely affects reproductive organ function. Future fertility is a primary concern of patients and their families. Variations in clinical practice are barriers to the timely implementation of interventions that preserve fertility. As part of the PanCareLIFE Consortium, in collaboration with the International Late Effects of Childhood Cancer Guideline Harmonization Group, we reviewed the current literature and developed a clinical practice guideline for fertility preservation in male patients who are diagnosed with childhood, adolescent, and young adult cancer at age 25 years or younger, including guidance on risk assessment and available methods for fertility preservation. The Grading of Recommendations Assessment, Development and Evaluation methodology was used to grade the available evidence and to form the recommendations. Recognising the need for global consensus, this clinical practice guideline used existing evidence and international expertise to rigorously develop transparent recommendations that are easy to use to facilitate the care of male patients with childhood, adolescent, and young adult cancer who are at high risk of fertility impairment and to enhance their quality of life.